Minimum bactericidal concentration of chemically synthesized silver nanoparticles against pathogenic Salmonella and Shigella strains isolated from layer poultry farms - Shimaa T. Omara, Mahmoud F. Zawrah, A. A. Samy (Journal of Applied Pharmaceutical Science, 2017)
The main objective of the present study is to find an appropriate in-vitro therapy to overcome clinically isolated antibiotic-resistant Salmonella and Shigella species from cases of layer poultry farms suffering from purulent dysentery and diarrhea. The present study demonstrated chemical synthesis of silver nanoparticles (AgNPs) via chemical reduction method and investigation for their antibacterial effect against the isolated bacteria by determining their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Of 32 examined samples, 8 (25%) antibiotic-resistant isolates were isolated and identified including: Shigella flexneri, Salmonella typhimurium (two), Salmonella poona, Shigella boydii, Salmonella montevideo, Shigella sonnei, Salmonella enteritidis. Spherical AgNPs of 10-25 nm in size were synthesized and the AgNPs at a concentration of 16 μgml-1 were found to have both bacteriostatic and bactericidal effects in the case of Salmonella montevideo (layer chicken egg), Shigella sonnei (layer chicken feces), Salmonella enteritidis (layer duck egg) however the AgNPs at a concentration of 8 μgml-1 were found to have both bacteriostatic and bactericidal effects in the case of Salmonella poona (layer chicken feces), Shigella boydii (layer chicken feces), Salmonella typhimurium (layer chicken feces).
Keywords: AgNPs, MIC, MBC, Salmonella, Shigella, antibacterial, poultry.